PENEGAKAN HUKUM TERHADAP PEREDARAN NARKOTIKA MELALUI DARK WEB - Ibrahim, Muhammad Habil Alif; Soekorini, Noenik; Aranggraeni, Renda (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Advances in information technology have created new challenges for law enforcement, one of which is the circulation of narcotics through the dark web, which is anonymous, cross-border, and difficult to trace. This study aims to analyze the reach of national law regarding perpetrators located outside Indonesia but conducting narcotics transactions with users in Indonesia, as well as to examine the application of the chain of custody and the validity of digital evidence for admissibility in court. The research method used is normative juridical, with a statutory and conceptual approach, complemented by field studies through interviews with law enforcement officials. The results indicate that the application of the principle of extraterritoriality, as stipulated in Articles 4 and 5 of the Criminal Code, provides the legal basis for reaching perpetrators abroad, supported by international cooperation through Mutual Legal Assistance, Interpol Red Notices, and joint operations. However, obstacles remain if there is no extradition treaty or the principle of double criminality is not met. In terms of evidentiary aspects, digital evidence can be recognized as valid evidence under the ITE Law if its collection and management follow strict chain of custody procedures, in accordance with the ISO/IEC 27037:2012 standard, including data integrity verification using hash values. This study recommends strengthening international cooperation, increasing the capacity of law enforcement officials in the field of digital forensics, standardizing digital forensics laboratories with international accreditation, and updating regulations in the Criminal Code (KUHP) and Criminal Procedure Code (KUHAP) to be more responsive to technology-based cross-border crimes